Cryopreservation and In Vitro banking: a cool subject – Preface from the editors - Ochatt, Sergio; Lambardi, Maurizio; Panis, Bartholomeus; Pathirana, Ranjith; Revilla, Maria Angeles; Wang, Qiao-Chun (Springer, 2021)
Plant breeding depends largely on having access to a wide variety of plant genetic resources, which are vulnerable to losses caused by biotic and abiotic threats when grown in the field or in a greenhouse. Thus, cryopreservation or in vitro banking is a safe strategy for long-term conservation of such genetic resources, which serves as back-up collections for field genebanks and reduces. For many species, encapsulation technologies can be a promising tool for the management of plant material of high quality, the production in nurseries of plants from in vitro culture, or the conservation of plant genetic resources. Such “synthetic seeds” proved to be of great value in the medium- (slow-growth storage) and long-term (cryopreservation) conservation of germplasm of fruit, ornamental, horticultural and forestry species in small spaces. However, more research is still needed. Cryopreservation projects must have clear goals, long-term funding, skilled technical support staff, necessary infrastructure, and well-defined procedures and protocols, so that they can be routinely implemented in plant cryobanks and help to establish backup collections of valuable plant genetic resources.